Enhanced light absorption in plasmonics-based MSM-PD with special design of subwavelength slit - Masouleh, F.; Das, Narottam; Rozati, S. (IEEE Computer Society, 2014)
A novel plasmonics-based metal-semiconductor-metal photodetector is introduced which dramatically modifies the light transmission spectra when the sub-wavelength central slit is not bare. FDTD method has been utilized to simulate the behavior of the device with significant responsivity.